Childhood abuse and adult cyberbullying victimization in Canada: The role of community belonging - Emily Earle; David Speed (PLoS ONE, 2025)
Childhood abuse is linked to a higher risk of experiencing cyberbullying victimization in adolescence and young adulthood, while a sense of belonging is associated with a reduced risk and buffers against the mental health effects of childhood trauma. However, there is a lack of Canadian research, particularly studies involving adult samples, examining the connection between childhood abuse and cyberbullying victimization in adulthood. The current study examined whether community belonging is a protective factor in the association between childhood abuse and cyberbullying victimization among adults. Data came from Cycle 34 of the Canadian General Social Survey ( n ≈ 14,000). Respondents were asked about the frequency in which they experienced seven childhood abuse variables and about the strength of their current community belonging. A binary logistic regression with bootstrap and person-level weights was conducted, while controlling for demographic variables. Results showed that: 1) for each childhood abuse variable, never experiencing that behaviour was associated with trivial-to-small effects for lower cyberbullying victimization in adulthood compared to those who experienced high levels of that behaviour; 2) as community belonging increased, the odds of adult cyberbullying victimization decreased; and 3) there were no significant moderating effects of community belonging; however, a pattern emerged suggesting that differences in cyberbullying victimization between those who did not experience a given abusive behaviour in childhood and those who did experience high levels of that behaviour were larger when community belonging was weaker and smaller when belonging was stronger. The current study highlights the importance of fostering community connections, for example, through programs, support groups, and volunteering, as a potential way of reducing the risk of cyberbullying among adults who have experienced childhood abuse.